How voluntary information sharing systems form: Evidence from a U.S. commercial credit bureau - José Liberti; Jason Sturgess; Andrew Sutherland (Queen Mary University of London, School of Economics and Finance, 2021)
We use the introduction of a U.S. commercial credit bureau to study when lenders adopt voluntary information sharing technology and the resulting consequences for competition and credit access. Our results suggest that lenders trade off access to new markets against heightened competition for their own borrowers. Lenders that do not share initially lose borrowers to competitors that share, which ultimately compels them to share and leads to the formation of an information sharing system. We find access to credit improves but only for high-quality borrowers in markets with greater lender adoption. Our results offer the first direct evidence on when financial intermediaries adopt information sharing technologies and how sharing systems form and evolve.
Keywords: G21; G23; G32; 330; information sharing; access to credit; financial intermediation; fintech; SMEs